2020
DOI: 10.3389/fchem.2020.606863
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Adaptive Variational Quantum Eigensolvers

Abstract: By design, the variational quantum eigensolver (VQE) strives to recover the lowest-energy eigenvalue of a given Hamiltonian by preparing quantum states guided by the variational principle. In practice, the prepared quantum state is indirectly assessed by the value of the associated energy. Novel adaptive derivative-assembled pseudo-trotter (ADAPT) ansatz approaches and recent formal advances now establish a clear connection between the theory of quantum chemistry and the quantum state ansatz used to solve the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Several implementations that followed focused on the utility of unitary coupled cluster methods and variations thereof. [7,[20][21][22][23] Other implementations demonstrated that the trial Ansatz need not be in UCC form to obtain chemical accuracy. [3] Eventually, variational methods were modified to be able to compute excited states as well.…”
Section: Quantum Chemistry Algorithmsmentioning
confidence: 99%
“…Several implementations that followed focused on the utility of unitary coupled cluster methods and variations thereof. [7,[20][21][22][23] Other implementations demonstrated that the trial Ansatz need not be in UCC form to obtain chemical accuracy. [3] Eventually, variational methods were modified to be able to compute excited states as well.…”
Section: Quantum Chemistry Algorithmsmentioning
confidence: 99%
“…We defer the description of constructing these linear combinations to prior work [30]. Various details on both ansatz operators have been reported previously [10,26]. An alternative to the fixed-depth ansatz operators above is an adaptive ansatz that changes the generating operator based on iterative evaluations of the energy estimate.…”
Section: Unitary Coupled Cluster Ansatz Operatorsmentioning
confidence: 99%
“…Previously, Claudino et al investigated the fidelity of several variational methods in approximating the ground state of few-electron molecular models [26]. Those results show that VQE methods with sophisticated ansatz circuits could approximate the ground electronic state with very high fidelity in the absence of circuit noise, depending on the ansatz and method of parameter selection.…”
Section: Introductionmentioning
confidence: 99%
“…The paradigmatic hybrid algorithm corresponds to the variational quantum eigensolver (VQE) [42,43], where a quantum computer is used to prepare parametrized quantum states and measure their energy, while classical optimization is used for finding the best variational parameters. This strategy enables quantum calculations with relatively noisy devices, and allows for numerous advances from the experimental [44][45][46][47][48][49][50][51][52] and theoretical [53][54][55][56][57][58][59][60][61][62][63][64][65][66] perspectives.…”
Section: Introductionmentioning
confidence: 99%